Does New York City Really have as Many Rats as People?. Issue 4 (3rd October 2014) - Auerbach, Jonathan
Abstract: Jonathan Auerbach, winner of the YSS/ Significance Young Statisticians Writing Competition, uses statistical methods to challenge an urban legend.